2014
DOI: 10.1007/s10147-014-0686-2
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy of low-dose 5-fluorouracil and cisplatin for advanced extramammary Paget’s disease

Abstract: Although the number of cases is limited and there is a bias because cases without clinical effects are less likely to be reported, this regimen might be considered a relatively effective option for advanced EPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 9 publications
1
49
0
Order By: Relevance
“…Tokuda et al . reviewed previous reports and retrospectively examined 22 patients with advanced EMPD who received FP . In their study, RR, mPFS and mOS were 59%, 5·2 months and 12 months, respectively.…”
Section: The Efficacy Of Chemotherapeutic Regimensmentioning
confidence: 99%
“…Tokuda et al . reviewed previous reports and retrospectively examined 22 patients with advanced EMPD who received FP . In their study, RR, mPFS and mOS were 59%, 5·2 months and 12 months, respectively.…”
Section: The Efficacy Of Chemotherapeutic Regimensmentioning
confidence: 99%
“…Currently, there is no consensus regarding the optimal chemotherapeutic regimen for treatment of metastatic EMPD. Numerous case reports and small retrospective studies have documented the efficacies of several regimens, including low‐dose 5‐fluorouracil + cisplatin (FP), 5‐fluorouracil, epirubicin, carboplatin, vincristine and mitomycin (FECOM) combination, the docetaxel (DTX) + S‐1 regimen and the cisplatin, epirubicin and paclitaxel combination regimen . However, treatment outcomes of these are not necessarily satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment outcomes of these are not necessarily satisfactory. While low‐dose FP and FECOM regimens show median progression‐free survival (PFS) of 5.2 and 6.5 months, respectively, both showed median overall survival (OS) of less than 1 year . Furthermore, patients undergoing treatment with these combination chemotherapies usually suffer from severe side‐effects and require repeated hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the response rate of DOC was 58% in a 12‐case study. Additionally, Tokuda et al . reported that the response rate of 5‐fluorouracil (5‐FU) and cisplatin (FP therapy) was 59% in a 22‐case study.…”
Section: Discussionmentioning
confidence: 99%